Perceptions and Interests of Senior High School Students on Petanque - Fajar Awang Irawan; Chakimah Anis Mawadati; Dhias Fajar Widya Permana (JUARA : Jurnal Olahraga, 2022)
Petanque characters tend to be sports requiring high accuracy, concentration, and focus. This study aimed to determine students' perceptions and interests in playing Petanque. This study uses qualitative research and data collection using interviews and questionnaires. Scores obtained from the questionnaire were then analyzed using descriptive percentages. The total sample in this study was 20 athletes from senior high school in Magelang Regency. All athletes have completed and agreed to participate by full informed consent. The perception of Petanque athletes in Magelang Regency in the Moderate category by 35%. Athletes' perceptions with the High average categories were 25%, and Low categories were 30%. The interest of petanque athletes in the Magelang Regency is in a Low category of 45%. While athletes' claim in the Very High category was 10%, the High category was 20%, and the Moderate category was 25. This study concluded that the perception of petanque athletes in Magelang Regency was included in the moderate category of 35%. At the same time, the interest level of petanque athletes in Magelang Regency is in the low category of 45%. Further research is expected to determine athletes' motivation and mentality in playing petanque.